Impacts of self-perceived malocclusion on the oral health-related quality of life of young adults in Malaysia / Zawani Mohd Tajudin - Zawani, Mohd Tajudin (2020)
Objectives: To assess the prevalence, severity and extent of impacts of self-perceived malocclusion on the oral health-related quality of life (OHRQoL) related to dental aesthetics among young Malaysian adults, to compare between those with and without self-perceived malocclusion and to investigate the influence of demographics on the outcome. Methods: Multi-stage random sampling method was used to recruit 589 subjects from tertiary institutions in Malaysia. Study instruments comprised the Aesthetic Component of the Index of Orthodontic Treatment Need (AC-IOTN) and Malaysian version of the Psychosocial Impact of Dental Aesthetics (PIDA) to measure selfperceived malocclusion and its impacts. Analyses included multifactorial ANOVA and Pearson correlation. Results: The response rate was 83.5%. Data analysis included complete data on 524 subjects. 92.6% of subjects with self-perceived malocclusion reported impacts on their OHRQoL. Psychological Impact was the most prevalent domain affected (75.8%), followed by Dental Self Confidence (59.4%), Social Impact (48.9%) and Aesthetic Concern (22.1%) domains. 28.6% subjects with self-perceived malocclusion reported significant impact on all domains while their mean severity PIDA scores were 43.9 (±16.1). Females had higher PIDA scores than males while Malays had higher PIDA scores than Indians (p>0.05) but the effect sizes were small. There was small yet significant interaction effect between gender and place of residence. Females in suburban and rural areas had significantly higher PIDA scores than their male counterparts. Conclusion: The study provided baseline data to demonstrate that Malaysian young adults were highly impacted by their perception of their malocclusion. Gender, race and residence influenced this effect.